An Analysis Of The Yemeni EFL Secondary Writing Curriculum: Approaches To Writing And Preparation For Higher Education - Fatima Othman Al-Hammadi
This study examines the overarching approaches to second language (L2) writing instruction as reflected in the Yemeni English as Foreign Language (EFL) secondary curriculum and how well this curriculum prepares students for the university level EFL writing in content areas. The data were collected by reviewing EFL curriculum documents such as the mandated EFL textbook in Yemeni public secondary schools and EFL workbook as well as observing EFL writing lessons at selected Yemeni secondary schools. The study examined the types of SLA theories, L2 writing instructional approaches, learner roles and teacher roles, the types of writing tasks and the emphasis on writing as a means to achieve the learning outcomes stipulated in the selected curriculum. The data for this study were analysed using manifest content analysis. The findings of the SLA theories, second language (L2) writing approaches, learner roles, and teacher roles reveal that there are misalignments in the theoretical grounding with regards to the communicative label of the selected curriculum. The misalignment of its theoretical underpinning in the selected curriculum is evidenced via the analysis of writing tasks in the EFL textbook and workbook. The findings show that the Yemeni EFL writing curriculum is highly cognitive in nature rather than communicative. In terms of preparing students for academic writing skills required for the tertiary level, writing skill is emphasised in the Yemeni EFL secondary curriculum over reading, listening, and speaking skills. However, the findings on the types of writing tasks and the level of cognitive demand of the writing tasks show that the students in the selected secondary level are not highly trained in writing the expository essays which require high cognitive demand. In contrast, more emphasis is given on training students with narrative writing tasks, which require low level cognitive demand. Knowing this, the Ministry of Education in Yemen, curriculum designers and teachers can realistically plan for the development of the secondary schools EFL writing curriculum and promote effective teaching and learning strategies that will equip students with the writing skills they need at the higher education level. Furthermore, the analytical framework with the proposed theoretical steps, and the empirical demonstration regarding the investigation of how well the EFL writing curriculum prepares students with the required academic writing skills for university, provides new directions for further theoretical development of linguistic studies in different EFL settings.